XML & related technologies - Kahate, Atul (Dorling Kindersley (India), 2009)
XML has become the standard for all kinds of integration and deployment of applications, regardless of the technology platform. XML & Related Technologies covers all aspects of dealing with XML, both from a conceptual as well as from a practical po.